2017
DOI: 10.1155/2017/7515409
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative PCR and Digital PCR for Detection ofAscaris lumbricoidesEggs in Reclaimed Water

Abstract: The reuse of reclaimed water from wastewater depuration is a widespread and necessary practice in many areas around the world and must be accompanied by adequate and continuous quality control. Ascaris lumbricoides is one of the soil-transmitted helminths (STH) with risk for humans due to its high infectivity and an important determinant of transmission is the inadequacy of water supplies and sanitation. The World Health Organization (WHO) recommends a limit equal to or lower than one parasitic helminth egg pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…A low infective dose combined with environmental hardiness and excretion of up to 200,000 ova per day in the faeces of infected hosts enhances the infectivity of Ascaris [3]. The use of raw and partially treated wastewater for agriculture is considered one of the major epidemiological factors for the prevalence of Ascaris infections [4]. Several studies have shown a significant relationship between Ascaris infection and exposure to treated and untreated wastewater [5].…”
Section: Methods Detailsmentioning
confidence: 99%
“…A low infective dose combined with environmental hardiness and excretion of up to 200,000 ova per day in the faeces of infected hosts enhances the infectivity of Ascaris [3]. The use of raw and partially treated wastewater for agriculture is considered one of the major epidemiological factors for the prevalence of Ascaris infections [4]. Several studies have shown a significant relationship between Ascaris infection and exposure to treated and untreated wastewater [5].…”
Section: Methods Detailsmentioning
confidence: 99%
“…The reuse of wastewater is widespread across the globe, especially in regions with water scarcity [1,2]. Recycled water can be utilised in irrigation but-if not treated effectively-can pose risk for public health owing to the pathogens present in the recycled water used for irrigation [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of their environmental hardiness, the WHO recommends parasitic helminth ova as an indicator of sanitary risk and water quality parameters [19,20]. WHO recommends an upper limit of one helminth ova per litre for recycled water to be judged suitable for irrigation and public use [2,21,22]. Based on such recommendations, the modified Bailenger method was suggested as a universal method for the detection of one helminth ova per 10 litres of recycled water for urban, agricultural, industrial, or environmental use [23,24].…”
mentioning
confidence: 99%
“…DNA-based diagnostic tests such as polymerase chain reaction (PCR) have proven to out-perform microscopy in their reliability to detect gastro-intestinal parasitic infections (Phuphisut et al ., 2014; Acosta Soto et al ., 2017). However, despite its high-throughput screening potential, PCR requires costly equipment (Kaisar et al ., 2017), and, therefore, has not been able to replace microscopy in the diagnosis of STH infections in large-scale epidemiological surveys or in disease control programs.…”
Section: Introductionmentioning
confidence: 99%